PERSEPSI SUAMI TERHADAP PERUBAHAN BENTUK TUBUH ISTRI SAAT KEHAMILAN USIA 20 – 40 MINGGU DI DESA CARAT KABUPATEN PASURUAN - Dewi, Aprilya Tunggo; Sari, Ika Puspita (NHM PRESS, 2021)
A pregnant wife needs a lot of support from various parties, especially from her husband and family. One of them is the attitude of the husband who pays more attention both physically and psychologically. A husband who always protects from work problems, increases affection, attention and accepts his wife's body shape during pregnancy. So, it can expedite the birth process of the baby. However, there are also some husbands who cannot accept changes in body shape when their wife is pregnant. The purpose of this study was to determine the husband's perception of changes in the wife's body shape during pregnancy aged 20-40 weeks. This research design uses a descriptive method. The sampling method used is total sampling. The samples taken were 21 respondents, namely husbands who had pregnant wives aged 20-40 weeks in Carat Village, Pasuruan Regency in March 2021. The research data were taken using a questionnaire. From the results of the study it can be concluded that the husband has a positive perception (71.20%) of changes in the wife's body shape during pregnancy aged 20-40 weeks in Carat Village, Pasuruan Regency. Based on the results of the research, a husband should always be faithful to accompany his wife, especially when the wife needs full support and attention, and always think positively about the changes that occur in a wife who is experiencing pregnancy so that she can expedite the delivery process that will take place.